Formulasi dan Karakterisasi Sediaan Spray gel Ekstrak Etanol Buah Pare (Momordica charantia L): Formulation dan Characterization of Ethanol Extracts Spray gel of Bitter Melon (Momordica charantia L.) Fruit - Nur Illiyyin Akib; Sabarudin; Sitti Raodah Nurul Jannah; Desi Nur Sholiha (Fakultas Farmasi Universitas Halu Oleo, 2023)
Bitter melon (Momordica charantia L.) fruit has been empirically used as an antibacterial and reported to have activity against acne-causing bacteria. This study aimed to formulate bitter melon ethanol extract in a spray gel preparation and test its activity against Staphylococcus epidermidis as one of the acne-causing bacteria. Pare fruit extract concentrations of 0.5%, 1%, and 2.5% are formulated into spray gel preparations with additional ingredients, Carbopol 940 0.1%, triethanolamine 0.5%, propylene glycol 15%, DMDM Hydantoin 0.6% and aquadest. The characterization of the physical properties of the spray gel preparation included organoleptic, homogeneity, pH, viscosity, and dry time test. The results showed that the spray gel preparation of ethanol extract of Pare fruit had a liquid texture, brownish-yellow colour, and distinctive odour and was homogeneous. The spray gel preparation also meets pH, viscosity and dry time requirements. The antibacterial activity of spray gel preparations resulted in a diameter response of potent and robust inhibition.